Resolve a equação do segundo grau
= -x
Soluções para a tarefa
Respondido por
2
x² - x = 0 (: x obtemos x = 0)
x - 1 = 0
x = 0 + 1
x = 1
S = {0, 1}
Anexos:
![](https://pt-static.z-dn.net/files/d13/9b7121834c16d3059bc7388ec7ab9474.jpg)
Respondido por
2
x.(x - 3) - x
----------- =
2
x² - 3x = 2.(-x)
x² - 3x = - 2x
x² - 3x + 2x = 0
x² - x = 0
x(x - 1) = 0
x = 0
x - 1 = 0
x = 1
R.: x = 0 e x = 1
----------- =
2
x² - 3x = 2.(-x)
x² - 3x = - 2x
x² - 3x + 2x = 0
x² - x = 0
x(x - 1) = 0
x = 0
x - 1 = 0
x = 1
R.: x = 0 e x = 1
Perguntas interessantes
História,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Biologia,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás